Study and development of structural optimization for 3D printing applications - Chin, Delwin Shao Feng (2018)
Structural optimization methods have always been an essential aspect in engineering design. It has been utilized extensively by industries to tweak existing designs to minimize or maximize various design variables. With the ever-growing development of additive manufacturing, end users are finding it more convenient to build on the benefits and ultimately produce geometrically complex optimized objects with ease. This report highlights the harmonious nature between topology optimization and additive manufacturing, by giving an overview on additive manufacturing as well as providing applications of the optimization tasks on ANSYS Workbench. The research study on this report will serve as a guide for operators to achieve the best results for their various applications in their different fields and industries using topology optimization on ANSYS Workbench while having a comprehensive overview of additive manufacturing and its applications.